Reinterpretation of the Non-Interference Norm in ASEAN Post-2021 Myanmar Coup: A Constructivist Analysis of Regional Governance Contestation - Saiman Pakpahan (CV Edujavare Publishing, 2026)
The Myanmar military coup on February 1, 2021, has tested ASEAN's core principles like never before. The long-standing non-interference policy, central to the “ASEAN Way,” has been challenged for its effectiveness in addressing Myanmar's political and humanitarian crises. This article explores how the crisis prompted a reinterpretation of the non-interference norm through debates among ASEAN leaders. Using a constructivist lens and the norm contestation framework, it analyzes official ASEAN documents, the 2021 Five-Point Consensus, and statements from member states. Early results suggest that the non-interference norm has evolved from a strict stance to a more conditional approach. The decision to exclude the Myanmar junta from top ASEAN meetings demonstrates a member-driven shift toward greater normative flexibility, which is unusual in the region’s history. Overall, this situation highlights a moment of norm contestation that prompts a modest reorganization of Southeast Asian regional governance.